The Effect of MEA Model Assisted by Audio Visual Media on Mathematical Problem Solving Ability of Elementary School Students - Yolanda Wulandari; Amir Luthfi; M. Syahrul Rizal (Edumaspul: Jurnal Pendidikan, 2021)
Abstract: This study aims to examine the effect of the Means Ends Analysis model assisted by audio-visual media on the mathematical problem solving ability of class V SD Negeri 012 Gading Sari, Tapung District. This type of research is quantitative with the Nonequivalent Control Group Design. The experimental class is class VA and the control class is class VB at SD Negeri 012 Gading Sari. Collecting research data using observation, tests and documentation. The results showed that the mathematical problem solving ability with the Means Ends Analysis (MEA) model assisted by audio-visual media is higher than the ability to solve mathematical problems with conventional models. This can be seen from the results of the t-test with a significance level of 5%, the value of sig (2-tailed) (0.000) < (0.05). This shows that the effect of the Means Ends Analysis (MEA) model audio-visual media assisted is better than conventional models, it can be concluded that there is an effect of the model Means Ends Analysis assisted by audio-visual media. Keywords: Means Ends Analysis (MEA) Model, Audio Visual Media, Mathematical Problem Solving Ability